The Development of Tourism Object of Love Beach in Cikoang, Takalar Regency - Musin, Mujali (Universitas Negeri Makassar, 2018)
This study aims to determine 1) the factors of geography that support the development of coastal tourism in the village Cikoang love.2) Obstacles encountered in the development of beach tourism in the village Cikoang love.3) The extent SWOT analysis of the development of coastal tourism in the village love Cikoang in the future.The population of tourists, managers and the public.The data presented in the form of primary data taken from the questionnaire